Palm tocotrienols reduce lipopolysaccharide-stimulated inflammatory responses of microglia - Tan, Shi Wei; Abdullah, Maha; Israf Ali, Daud Ahmad; Vidyadaran, Sharmili (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2016)
Introduction: The potential immunoregulatory effects of tocotrienols, the less studied form of vitamin E, had not been determined for microglia until our last publication showcased primary evidence of palm tocotrienols limiting microglia activation, explicitly by inhibiting nitric oxide (NO) production. Here we further explored the nitrite scavenging activity of the two most potent NO-reducing tocotrienol isoforms - δ-tocotrienol and Tocomin®50% (contains a spectrum of tocotrienols and α-tocopherol) based on their inhibitory effects on NO production and also their effects on CD40 (a microglial co-stimulator molecule) expression of BV2 microglia. Methods: BV2 cells were treated with two different doses of tocotrienols (δ-tocotrienol: 3.96 μg/mL and 19.80 μg/mL; Tocomin®50%:47.50 μg/mL and 237.50 μg/mL) followed by stimulation with 1μg/mL of lipopolysaccharide (LPS). A chemical scavenging assay was conducted to study the nitrite scavenging activity of δ-tocotrienol. Together with Tocomin®50%, we also determined their effects on CD40 expression of BV2 microglia via flow cytometry. Results: We demonstrate that the inhibitory effect of tocotrienols on NO production by microglia is not attributed to their nitrite scavenging activity. Additionally, tocotrienols also reduced the expression of the microglial co-stimulator molecule, CD40. Conclusions: Our data aids the further characterisation of the actions of tocotrienols on microglia, offering insight into the potential modulatory properties of palm tocotrienols on microglial inflammatory responses within the central nervous system (CNS).